One Health approach for West Nile virus surveillance in the European Union: relevance of equine data for blood safety - Young, Johanna J (Euro Surveill, 2019)
West Nile virus (WNV) infection is notifiable in humans and equids in the European Union (EU). An area where a human case is detected is considered affected until the end of the mosquito transmission season (week 48) and blood safety measures have to be implemented. We used human and equine case notifications between 2013 and 2017 to define the WNV distribution in the EU and to investigate the relevance of using equine cases as a complementary trigger for blood safety measures. Adding areas with equine cases to the definition of an affected area would have a major impact on blood safety measures. Adding areas with equine cases where human cases have been reported in the past would increase the timeliness of blood safety measures with only a limited impact. Although the occurrence of human and/or equine cases confirms virus circulation in the EU, no evidence was found that occurrence of equine cases leads to human cases and vice versa. We conclude that information about equine data should contribute to raising awareness among public health experts and trigger enhanced surveillance. Further studies are required before extending the definition of affected areas to areas with human and/or equine cases.